Algoritma Honey Encryption dalam Sistem Pendataan Sertifikat Tanah dan Bangunan di Universitas Malikussaleh - Sujacka Retno; Novia Hasdyna; Mutasar Mutasar; Rozzi Kesuma Dinata (Faculty of Computer Science, University of Jember, 2020)
The management of Land and Building Certificates at Universitas Malikussaleh is still using a manual library in Biro Perlengkapan which contains some problem whereas it can be burned accidentally refers to fire case in 2017 in Rektorat Building at Universitas Malikussaleh. Given the problem faced by the staff in Biro Perlengkapan, the authors idea is to create a database-based data processing system, the authors designed an integrated information system which be able to anticipated such problem in the future and saving time to collecting important certificates such Land and Building Certificates at Universitas Malikussaleh and protecting them with Honey Encryption algorithm. The information system based on desktop and works as a client-server system. The result of this research provide that the honey encryption algorithm can protect the data and it can solve the problem in management system of land and building certificates.